County‐Level Variation in Hepatitis C Virus Mortality and Trends in the United States, 2005‐2017. Issue 2 (20th July 2021) - Hall, Eric W.; Schillie, Sarah; Vaughan, Adam S.; Jones, Jeb; Bradley, Heather; Lopman, Ben; Rosenberg, Eli S.; Sullivan, Patrick S.
Abstract : BACKGROUND AND AIMS: Since 2013, the national hepatitis C virus (HCV) death rate has steadily declined, but this decline has not been quantified or described on a local level. APPROACH AND RESULTS: We estimated county‐level HCV death rates and assessed trends in HCV mortality from 2005 to 2013 and from 2013 to 2017. We used mortality data from the National Vital Statistics System and used a Bayesian multivariate space–time conditional autoregressive model to estimate age‐standardized HCV death rates from 2005 through 2017 for 3, 115 U.S. counties. Additionally, we estimated county‐level, age‐standardized rates for persons <40 and 40+ years of age. We used log‐linear regression models to estimate the average annual percent change in HCV mortality during periods of interest and compared county‐level trends with national trends. Nationally, the age‐adjusted HCV death rate peaked in 2013 at 5.20 HCV deaths per 100, 000 persons (95% credible interval [CI], 5.12, 5.26) before decreasing to 4.34 per 100, 000 persons (95% CI, 4.28, 4.41) in 2017 (average annual percent change = −4.69; 95% CI, −5.01, −4.33). County‐level rates revealed heterogeneity in HCV mortality (2017 median rate = 3.6; interdecile range, 2.19, 6.77), with the highest rates being concentrated in the West, Southwest, Appalachia, and northern Florida. Between 2013 and 2017, HCV mortality decreased in 80.0% (n = 2, 274) of all U.S. counties with a reliable trend estimate, with 25.8% (n = 803) of all counties experiencing a decrease larger than the national decline. CONCLUSIONS: Although many counties have experienced a shift in HCV mortality trends since 2013, the magnitude and composition of that shift have varied by place. These data provide a better understanding of geographic differences in HCV mortality and can be used by local jurisdictions to evaluate HCV mortality in their areas relative to surrounding areas and the nation.